Впровадження технологій доповненої реальності в системах авіоніки - Зуєва, А. Д. (ХНУРЕ, 2025)
Modern aviation technologies are actively developing, contributing to the improvement of safety, accuracy and efficiency of flights. One of the promising areas is the use of augmented reality (AR), which allows integrating digital elements into the physical environment. This significantly improves the interaction of pilots, controllers and technical personnel with aviation systems. Augmented reality allows you to display important flight information in a clear form, reducing cognitive load and speeding up the decision-making process. The introduction of AR into cockpits, control centers, and maintenance systems opens up new opportunities for aviation development.
Keywords: авіоніка; aviation technologies